Improvement in glycemia after glucose or insulin overload in leptin-infused rats is associated with insulin-related activation of hepatic glucose metabolism. Issue 1 (December 2016) - Burgos-Ramos, Emma; Canelles, Sandra; Frago, Laura; Chowen, Julie; Arilla-Ferreiro, Eduardo; Argente, Jesús; Barrios, Vicente
Abstract Background Insulin regulates glucose homeostasis through direct effects on the liver, among other organs, with leptin modulating insulin's hepatic actions. Since central leptin may modify insulin signaling in the liver, we hypothesized that leptin infusion activates hepatic glycogen synthesis following peripheral administration of a bolus of glucose or insulin, thus regulating glycemia. Findings Oral glucose and intraperitoneal insulin tolerance tests were performed in control, intracerebroventricular leptin-treated and pair-fed rats during 14 days. An improvement in glycemia and an increase in hepatic free glucose and glycogen concentrations after glucose or insulin overload were observed in leptin-treated rats. In order to analyze whether the liver was involved in these changes, we studied activation of insulin signaling by Western blotting and multiplex bead immunoassay after leptin infusion. Our studies revealed an increase in phosphorylation of insulin receptor substrate-1 and Akt in leptin-treated rats. Examination of parameters related to glucose uptake and metabolism in the liver revealed an augment in glucose transporter 2 and a decrease in phosphoenolpyruvate carboxylase protein levels in this group. Conclusions These results indicate that central leptin increases hepatic insulin signaling, associated with increased glycogen concentrations after glucose or insulin overload, leading to an improvement in glycemia.